A Software Multi-GNSS Receiver Implementation for the Indian Regional Navigation Satellite System. Issue 2 (3rd March 2016) - Thombre, Sarang; Bhuiyan, Mohammad Zahidul Hasan; Söderholm, Stefan; Kirkko-Jaakkola, Martti; Ruotsalainen, Laura; Kuusniemi, Heidi
ABSTRACT: The Indian Regional Navigation Satellite System (IRNSS) is currently under development with four out of the total planned seven satellites deployed in space. The Department of Navigation and Positioning of the Finnish Geospatial Research Institute (FGI) has been an early adopter of this system in Europe through the development of its software-based multi-frequency multi-GNSS receiver, called FGI-GSRx. This paper presents the results of the first comprehensive IRNSS receiver implementation in Finland, if not in Europe, using the FGI-GSRx receiver. Following a brief description of the IRNSS system, the paper presents the receiver architecture, including the acquisition and tracking stages, and position computation. The results show that IRNSS satellites when used in multi-GNSS positioning can be beneficial in augmenting other satellite systems over north and east Europe. These benefits are expected to grow as more IRNSS satellites are deployed in space in the future. Therefore, the impact of these results is interesting to the positioning, navigation, and timing community even outside the intended service area of IRNSS.